One-part alkali-activated mortars based on clay brick waste, natural pozzolan waste, and marble powder waste - Kübra Ekiz Barış (Journal of Sustainable Construction Materials and Technologies)
In Türkiye, waste clay bricks (WCB) comprise significant construction and demolition waste. Most research is based on producing WCB-based two-part alkali-activated materials (AAM). Compared to their conventional, two-part alkali-activated counterparts, one-part AAM offers several advantages, such as being more practical, safe, and easy to use. Thus, they may be an excellent choice for commercial construction applications and on-site casting. However, research data on producing WCB-based one-part alkali-activated mortars is limited. The relatively low reactivity of WCB can be increased by replacing WCB with ground granulated blast-furnace slag (GGBS) and fly ash (FA). Unlike these by-products, Nevşehir pozzolan (NP) and marble powder (MP), which are produced as wastes during the stone-cutting process, may be evaluated to produce AAM. This study aims to assess the production possibilities of WCB-based one-part alkali-activated mortar, determine the optimum substitution ratios with NP and MP o improve the mechanical properties, and determine the effects of the curing period up to 365 days. Results showed that the optimum NP substitution ratio was 50%, which increased reaction development, microstructure compactness, and mechanical properties. The highest CS (UV) (3.70 km/s) and compressive strength (CS) (21.58 MPa) were obtained in 25WC-B:75MP-containing samples. The increase in properties with the curing period was especially high in the first 28 days.